2,4m*(-3n)=? -7a-9b+a+11b=? -8a-12b+5a+17b=? a-(a-8)+(12+a)=? a-(a+5)+(-7+a)=? -3*(c-5)+6*(c+3)=? -5*(y-4)+(y+5)=?

БезумныйКами666 БезумныйКами666    3   15.04.2019 16:29    1

Ответы
MuclePan MuclePan  29.05.2020 13:26

Пошаговое объяснение:

-2,4m*(-3n)= 7,2mn

-7a-9b+a+11b= -6a + 2b

-8a-12b+5a+17b= -3a + 5b

a-(a-8)+(12+a)= a - a + 8 + 12 + a = a + 20

a-(a+5)+(-7+a)= a - a - 5 - 7 + a = a - 12

-3*(c-5)+6*(c+3)= -3c + 15 + 6c + 18 = 3c + 33

-5*(y-4)+(y+5)= -5y + 20 + y + 5 = -4y + 25

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика